Interactions between SERPINA1 PiMZ genotype, occupational exposure and lung function decline. Issue 4 (8th November 2013) - Mehta, A J; Thun, G A; Imboden, M; Ferrarotti, I; Keidel, D; Künzli, N; Kromhout, H; Miedinger, D; Phuleria, H; Rochat, T; Russi, E W; Schindler, C; et al.
Abstract : Objectives: We evaluated interactions between SERPINA1 PiMZ genotype, associated with intermediate α1-antitrysin deficiency, with outdoor particulate matter ≤10 µm (PM10 ), and occupational exposure to vapours, dusts, gases and fumes (VGDF), and their effects on annual change in lung function. Methods: Pre-bronchodilator spirometry was performed in 3739 adults of the Swiss Cohort Study on Air Pollution and Lung Disease in Adults (SAPALDIA) for whom SERPINA1 genotypes were available. At baseline in 1991, participants were aged 18–62 years; follow-up measurements were conducted from 2001 to 2003. In linear mixed regression models of annual change in lung function, multiplicative interactions were evaluated between PiMZ genotype (PiMM as reference) and change in PM10 (μg/m 3 ), and VGDF exposure (high-level, low-level or no exposure as reference) during follow-up. Results: Annual declines in forced expiratory flow at 25–75% of forced vital capacity (FEF25–75% ) (−82 mL/s, 95% CI −125 to −39) and forced expiratory volume in 1 s over forced vital capacity (FEV1 /FVC) (−0.3%, 95% CI −0.6% to 0.0%) in association with VGDF exposure were observed only in PiMZ carriers (Pinteraction <0.0001 and Pinteraction =0.03, respectively). A three-way interaction between PiMZ genotype, smoking and VGDF exposure was identified such that VGDF-associated FEF25–75% decline was observed only in ever smoking PiMZ carriers (Pinteraction =0.01). No interactions were identified between PiMZ genotype and outdoor PM10 . Conclusions: SERPINA1 PiMZ genotype, in combination with smoking, modified the association between occupational VGDF exposure and longitudinal change in lung function, suggesting that interactions between these factors are relevant for lung function decline. These novel findings warrant replication in larger studies.